A abordagem socioantropológica de Sophie Poirot-Delpech - Sara Ramos (Universidade do Porto, 2007)
The aim of this paper is to present the work of Sophie Poirot-Delpech. Through her research, the author has contributed to the development of a specific tradition in the sociological domain - the social-anthropology of technique. In this approach (that has benefited from the contributions of other authors, particularly Alain Gras, Gérard Dubey, Caroline Moricot, Victor Scardigli) we try to identify convergence points with organizational psychologists´ practice, namely, the centrality of the real; participative action; and the importance of context. Particular attention is paid to the concepts and methods adopted, in order to emphasize the contributions that this tradition brings to the research on organizational psychology. Also accentuated is the exercise of contextualizing human activity, its historical character and the relevance of its continuous (re)construction as imperatives to the understanding of it.